Islamic Moral Education in Shaping the Character of Muslim Identity in the Millennial Era - Fairuz Zahira; Alya Shofi Hamida; Annisa Sarvina Tsabit; Naila Nasywa Fauzia; Ruqoyyah Romadhoni; Febryan Hidayat (Walidem Institute and Publishing (WIP), 2024)
This study aims to discuss the concept and role of akhlak education in Islam that shapes the character of Muslim identity in the millennial era. This study used qualitative research methods and library research. In this study, the data sources used previously came from relevant literature and references. As a literature review, research is carried out by collecting and reviewing various journals that have been researched by previous research and have been published and can be trusted to obtain data through journal reviews and scientific papers. This study discusses the concept of moral education in Islam where moral education is very important for every individual and group leading to the formation of noble morals, strong personalities, good morals, and right attitudes in the younger generation. The roles and challenges of Muslim women in the millennial era include a Muslim woman having a role as a mother and madrasah and improving the quality and honour of herself because Muslim women in the millennial era have challenges that sometimes a ban becomes a habit. Islamic moral education has a very important role in shaping good character and ethics, as well as strengthening the identity of Muslim women. Through this Islamic moral education, Muslim individuals are expected to learn and apply morals according to Islamic teachings in every aspect of their lives, both about Allah Subhanahu wa Ta'ala, fellow humans, and the surrounding environment.